Land Rights Movements in Nepal: Investigating Mobilization Strategies within a Political Landscape - Gurung, Ram (SMC Journal of Sociology, 2024)
This paper explores nations' political influence on social movement organizations. It focuses on the activities of National Land Rights Forum (NLRF), the largest land rights organization of Nepal. Effective mobilization of movement depends on organization's ability to align with the current political landscape, but is less emphasized by the global south social movement studies, which are focused on analyzing historical triggers and socioeconomic consequences with references to state policies. This paper takes survey-based open-ended interviews with 27 stakeholders, including the leaders and participants of NLRF’s land rights movement. The NLRF’s experiences on mobilization provided a strategic understanding of its adaptation to country's political milieu by leveraging the state-initiated major political events, which could be seen as opportunities to incorporate their concerns with state agendas. Furthermore, the Maoist-led insurgency in the past had fueled for the land rights movements, particularly the NLRF’s priority in organizing and unifying individuals who had similar political and economic identities. The mobilization strategies for land rights movement highlight the contextual variation on how current political landscape shapes the adaptive systems and practices of movement organizations.